Reflections on Direct Access to the African Court on Human and Peoples’ Rights: A Cul De Sac? - Tambasi Netya , Sidney; Gathoni Miano, Cynthia (Strathmore Law Review, 2021)
Individuals and NGOs can directly access the African Court on Human and Peoples’ Rights if the state against which a case has been filed has made an optional declaration granting this access. Alternatively, they can access the Court if the African Commission on Human and Peoples’ Rights refers communications to it. However, two main barriers have riddled this structure. One, the few states that had made the optional declaration have begun to rapidly withdraw from it. Two, the African Commission, which was expected to mitigate such a situation where few states are making the optional declaration, is hardly referring cases to the Court. This paper examines these two barriers in tandem. It argues that if this status quo is sustained, then, sooner rather than later, this path treaded may lead the African human rights system to a cul-de-sac – back to a one tier system, composed of an accessible Commission and a Court inaccessible to both individuals and NGOs. Drawing lessons from the European and Inter-American Human Rights system, it recommends preventing this eventuality by amending the African Commission’s 2020 Rules of Procedure to provide for a default procedure of referral of cases from the Commission to the Court.